A Quasi-Experimental Study to Assess the Effectiveness of Sodium Bicarbonate Oral Irrigation on Oral Mucositis among the Cancer Patients who Admitted at Cancer Hospital and Research Institute, Gwalior City (Madhya Pradesh) - Varsha Prahapati; Farukh Khan (Indian Journal of Nursing Sciences, 2025)
Background: According to epidemiological data, head-and-neck cancers constitute for 12% of all malignancies in the world. It is estimated that a total of 4,00,000 cases of the mouth and throat, 1,60,000 cases of laryngeal cancer, and 3,00,000 people die each year. Aim: The aim of the study is to assess the effect of sodium bicarbonate (SB) oral irrigation on oral mucositis. Methods: The evaluative research approach is applied; the research design is quasi-experimental with experimental group pre-test, treatment and post-test and control group pre-test and post-test design. The study was conducted in the cancer hospital research institute in Gwalior, Madhya Pradesh. The target population was cancer patients, receiving five-point rating scale related to oral mucositis during the period of study. The sample of study comprises 60 (30 control and 30 experimental groups) cancer patients, fulfilling the sample criteria. Non-probability convenient sampling technique was adopted. Results: The pre- and post-test mean oral mucositis score of control group was 72 and standard deviation was 25.69. In experimental group, pre-test mean oral mucositis score was 78.69 and standard deviation score was 18.64 and post-test mean score was 53.43 and standard deviation was 16.63. The “t” test score of the control group was 0 and the probability was 2.05 according to the degree of freedom was 29, which indicates that it is no significant score. In the experimental group, the “t” test score was 30.07 and the probability was 2.05, according to the degree of freedom was 29, which indicates that it is a significant score. Conclusion: The results showed that there is an effect of SB oral irrigation on oral mucositis in oral cancer patients.